The MANAJEMEN BIMBINGAN DAN KONSELING BERBASIS PENDEKATAN RESTORATIF DALAM PENANGANAN KEDISIPLINAN SISWA - Ririn Novita Sari; Ririn Inayatul Mahfudloh (Jurnal Manajemen Pendidikan, 2026)
Student discipline issues remain a challenge in the management of vocational high schools. Various violations indicate that a punishment-based disciplinary approach has not been effective in fostering sustainable disciplined behavior. Therefore, an educational strategy is needed through guidance and counseling services integrated with a restorative approach. This study aims to analyze the management of guidance and counseling services in addressing student discipline issues and to examine the implementation of a restorative approach at State Vocational High School 1 Sarirejo. The method used in this study is qualitative, employing a case study approach through observation and interviews with the school principal, guidance and counseling teachers, and students. The results of this study indicate that service management is implemented through planning based on student needs, the application of a restorative approach through counseling, dialogue, and mediation, as well as evaluation through monitoring behavioral development and case documentation. The novelty of this study lies in the integration of guidance and counseling service management with restorative practices as a humanistic and participatory model of discipline development.